2019
DOI: 10.1111/ger.12408
|View full text |Cite
|
Sign up to set email alerts
|

Functional dentition, dietary intake and nutritional status in Thai older adults

Abstract: Objectives To explore the relationship between functional dentition and nutritional status among Thai older adults, and the role of nutrient intake in this association. Background Evidence on the interplay between tooth retention, diet and nutritional status is still inconclusive, with most evidence coming from Western countries. Methods Seven hundred and eighty‐eight Thai adults, aged 60+ years, living in Phetchaburi Province, Thailand, participated in this cross‐sectional study. Data were collected through q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
(33 reference statements)
2
15
0
Order By: Relevance
“…The selected studies included 23 observational studies [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ] (17 cross-sectional [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [33] , [34] , [35] , 37 , 38 , 40 , 42 , 43 , 45 , 46 ] and 6 longitudinal designs [ 28 , 30 , 32 , 36 , 39 , 44 ]) and 4 interventional studies [ [47] , [48] , [49] , [50] ]. The number of study participants ranged between 32 and 28,738.…”
Section: Resultsmentioning
confidence: 99%
“…The selected studies included 23 observational studies [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ] (17 cross-sectional [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [33] , [34] , [35] , 37 , 38 , 40 , 42 , 43 , 45 , 46 ] and 6 longitudinal designs [ 28 , 30 , 32 , 36 , 39 , 44 ]) and 4 interventional studies [ [47] , [48] , [49] , [50] ]. The number of study participants ranged between 32 and 28,738.…”
Section: Resultsmentioning
confidence: 99%
“…All participants had normal scores in the abbreviated mental test score (>8 out of 10) [21] and in the activities of daily living questionnaire (≥12 out of 20) [22]. Participants who could not communicate or had disabling conditions were excluded [23]. All participants were invited to a follow-up examination a year later.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals were classified as having non-FD without dentures (reference group), non-FD with dentures or FD (i.e., having all 6 anterior FTU plus at least 4 posterior FTU, not necessarily symmetrical). If either tooth in a FTU had evidence of severe caries (root remnants) or severe mobility, the FTU was not counted as part of the requirement for a FD [23]. Seventy-eight participants were re-examined for reliability assessment.…”
Section: Data Collectionmentioning
confidence: 99%
“…Tooth loss is associated with decreased chewing ability, unfavourable changes in food choices, and poor quality and quantity of diet, which can lead to undernutrition among older adults. [1][2][3] Moreover, tooth loss affects systemic health and is a predictor of disability, deterioration in quality of life and premature death. 4,5 Osteoporosis is a systemic skeletal disorder that primarily affects women.…”
Section: Introductionmentioning
confidence: 99%
“…Both tooth loss and osteoporosis are common in elders and considered serious health problems. [1][2][3]6 Previous studies have reported significant associations of low BMD and osteoporosis with tooth loss. Older women with low BMD or osteoporosis are reported to have fewer teeth.…”
Section: Introductionmentioning
confidence: 99%